Petition to replace current OGTT criteria for diagnosing prediabetes with the 1-hour post-load plasma glucose ≥ 155 mg/dl (8.6 mmol/L). (December 2018) - Bergman, Michael; Manco, Melania; Sesti, Giorgio; Dankner, Rachel; Pareek, Manan; Jagannathan, Ram; Chetrit, Angela; Abdul-Ghani, Muhammad; Buysschaert, Martin; Olsen, Michael H.; Nilsson, Peter M.; Medina, José Luis; et al.
Abstract: Many individuals with prediabetes, as presently defined, will progress to diabetes (T2D) despite the considerable benefit of lifestyle modification. Therefore, it is paramount to screen individuals at increased risk with a more sensitive method capable of identifying prediabetes at an even earlier time point in the lengthy trajectory to T2D. This petition reviews findings demonstrating that the 1-hour (1-h) postload plasma glucose (PG) ≥ 155 mg/dl (8.6 mmol/L) in those with normal glucose tolerance (NGT) during an oral glucose tolerance test (OGTT) is highly predictive for detecting progression to T2D, micro- and macrovascular complications and mortality in individuals at increased risk. Furthermore, the STOP DIABETES Study documented effective interventions that reduce the future risk of T2D in those with NGT and a 1-h PG ≥ 155 mg/dl (8·6 mmol/L). The 1-h OGTT represents a valuable opportunity to extend the proven benefit of diabetes prevention to the sizeable and growing population of individuals at increased risk of progression to T2D. The substantial evidence provided in this petition strongly supports redefining current diagnostic criteria for prediabetes with the elevated 1-h PG level. The authors therefore advocate a 1-h OGTT to detect prediabetes and hence, thwart the global diabetes epidemic.